2015
DOI: 10.1007/s10334-014-0479-7
|View full text |Cite
|
Sign up to set email alerts
|

The separation of Gln and Glu in STEAM: a comparison study using short and long TEs/TMs at 3 and 7 T

Abstract: Based on the optimal separation for Gln and Glu, a short TE/TM at 7 T is proposed for future in vivo Gln and Glu acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It would appear that a combination of LCModel peak fitting and spectral editing is a better choice to obtain more accurate quantification of metabolites that suffer from overlapping peaks. However, a study at 7 T, comparing phantom quantification of Gln and Glu obtained with short‐ and long‐TE STEAM sequences, demonstrated that the higher SNR, short‐TE spectra yielded comparable quantification with that obtained from the long‐TE spectra with lower CRLB values . In addition, T 2 values of metabolites can change with disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would appear that a combination of LCModel peak fitting and spectral editing is a better choice to obtain more accurate quantification of metabolites that suffer from overlapping peaks. However, a study at 7 T, comparing phantom quantification of Gln and Glu obtained with short‐ and long‐TE STEAM sequences, demonstrated that the higher SNR, short‐TE spectra yielded comparable quantification with that obtained from the long‐TE spectra with lower CRLB values . In addition, T 2 values of metabolites can change with disease .…”
Section: Discussionmentioning
confidence: 99%
“…However, a study at 7 T, comparing phantom quantification of Gln and Glu obtained with short-and long-TE STEAM sequences, demonstrated that the higher SNR, short-TE spectra yielded comparable quantification with that obtained from the long-TE spectra with lower CRLB values. 67 In addition, T 2 values of metabolites can change with disease. 68,69 Therefore, if T 2 cannot be determined, a short-TE method may be a better alternative.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased spectral dispersion at an ultra‐high field, the increased ability to assess Glu and GABA from the same measurement session provides a more reliable assessment of the association of these neurotransmitters with rsFC in the same individuals. Additionally, the validity of the applied measurement strategy in this study has been investigated (Dou et al, 2015), particularly in the human cingulate cortex subregions (Dou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A single‐average water signal served as the internal reference for quantification and eddy‐current correction. The positioning of the two MRS voxels that followed anatomical landmarks is described in previous papers from our group (Dou et al, 2013; Dou et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The modulation in the STEAM sequence arising from scalar coupling is governed by both TE and mixing time (TM). The optimisation of the STEAM sequence timing parameters has been investigated for the improved acquisition of scalar‐coupled metabolites at ultra high‐field, such as glutamate 12‐14 . For lactate measurement, previous work reported an analytical expression derived for the STEAM signal modulation in a weakly‐coupled spin system of the lactate form, 15 AX 3 , where A corresponds to the proton in the methine group and X to those in the methyl group.…”
Section: Introductionmentioning
confidence: 99%